Janus‐like BxC/C Quantum Sheets with Z‐Scheme Mechanism Strengthen Tumor Photothermal‐Immunotherapy in NIR‐II Biowindow. Issue 6 (23rd April 2022) - Lu, Shi‐Yu; Wang, Jingjing; Wang, Xingyue; Yang, Wenting; Jin, Meng; Xu, Luen; Yang, Huawei; Ge, Xiaoxiao; Shang, Changshuai; Chao, Yuguang; Zhou, Lei; Yin, Kun; et al.
Abstract: Carbon dots (CDs) are one of the most popular photothermal agents (PTAs) as a noninvasive strategy for tumor treatment. However, because of the inherent dominant fluorescent emission, the CDs‐based PTAs hardly achieve a single photothermal conversion, which causes low photothermal conversion efficiency and poor photothermal performance. In this regard, finding a new CDs‐based material system to greatly restrain its fluorescence to enhance its photothermal conversion efficiency is highly required, however, it is still a grand challenge. Herein, a kind of Z‐scheme CDs‐based PTAs consisting of 2D ultrathin nonmetallic Bx C/C Janus quantum sheets (Bx C/C JQSs) is reported to greatly enhance the photothermal conversion efficiency. It is demonstrated that the heterogeneous growth of Z‐scheme Bx C/C JQSs enables the NIR‐driven quick injection of hot electrons from C into the conjugated Bx C, realizing a single conversion of light to heat, and resulting in a high photothermal conversion of 60.0% in NIR‐II. Furthermore, these new Z‐scheme Bx C/C‐polyethylene glycol JQSs display outstanding biocompatibility and show effective tumor elimination outcome both in vitro and in vivo through the synergistic photothermal‐immunotherapy in the NIR‐II biowindow with undetectable harm to normal tissues. Abstract : A kind of Z‐scheme carbon dot‐based photothermal agent consisting of 2D ultrathin nonmetallic Bx C/C Janus quantum sheets is reported here to solve the limitation of fluorescence on photothermal conversion. The heterogeneous growth of Z‐scheme Bx C/C enables the laser‐driven quick injection of hot electrons from C into Bx C, realizing ultra‐high photothermal conversion of 60.0% in the NIR‐II biowindow for tumor elimination.